2013
DOI: 10.3109/09273972.2013.787634
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Visual Acuity in Patients with Dementia using Teller Acuity Cards

Abstract: An alternative method for assessing visual function in patients with Alzheimer's disease, even at early stages, is of utmost relevance not only for monitoring disease progression, but also to quantitatively determine the impact of eye treatments and determine potential visual loss, guiding optical and non-optical strategies for optimal use of residual vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…43 More recently, Teller cards and Lea symbols were used to measure grating and recognition acuity respectively, in subjects with AD (n = 20) and age-matched controls (n = 24). 45 The results indicated that VA measured with the two techniques were well correlated, in agreement with earlier data. 43 Finally, VA has been compared using six validated acuity charts in older residents (n = 30) from long-term care units suffering from mild to severe dementia.…”
Section: Visual Acuitysupporting
confidence: 81%
“…43 More recently, Teller cards and Lea symbols were used to measure grating and recognition acuity respectively, in subjects with AD (n = 20) and age-matched controls (n = 24). 45 The results indicated that VA measured with the two techniques were well correlated, in agreement with earlier data. 43 Finally, VA has been compared using six validated acuity charts in older residents (n = 30) from long-term care units suffering from mild to severe dementia.…”
Section: Visual Acuitysupporting
confidence: 81%
“…The set consisted of 15 cards with gratings ranging in spatial frequency from 0.32 to 38 cycles/cm in half-octave steps as well as a low vision card and a blank gray card. The infant was assessed using the standard procedure of the operation manual [26, 27]. For verbal children, BCVA was measured and recorded using a LEA Symbols 13-Line Translucent Distance Chart (Good-Lite Co., IL, USA) according to the standard procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The set consisted of 15 cards with gratings ranging in spatial frequencies from 0.32 cycles/cm to 38 cycles/cm in half-octave steps as well as a low vision card and a blank gray card. The infant was assessed using the standard procedure of the operation manual [18, 19]. For verbal children, visual functions were measured and recorded using a LEA Symbols 13-Line Translucent Distance Chart (Good-Lite Co., IL, USA) according to the standard procedure.…”
Section: Methodsmentioning
confidence: 99%